Pelatihan Pembuatan Website dan Youtube sebagai Media Pengenalan Potensi Desa secara Online - Bashori, Hasan (LP2M INSURI Ponorogo, 2023)
The purpose of the website and YouTube creation training activities in Jatisari village is to introduce village potential online. In this community service activity using the Community Based Research (CBR) method with the Forum Group Discussion (FGD) approach. There are several ways to implement the FGD method, including 1) conducting outreach to the village government, PKK women, MSMEs and farmer groups; 2) workshops on developing village potential management with the village government, PKK women, MSMEs and farmer groups; 3) website and youtube creation training. The process of creating a website and YouTube is in collaboration with the village government, PKK women, MSMEs, farmer groups and assisted by SDGs KKN students at Yudharta University, Pasuruan. The results of the training are in the form of website links and YouTube accounts for Jatisari village. With the existence of a village website and YouTube it is hoped that it can become a medium to be able to introduce the potential that exists in Jatisari village to the wider community online.